2016
DOI: 10.1038/srep34991
|View full text |Cite
|
Sign up to set email alerts
|

Functional visualization and disruption of targeted genes using CRISPR/Cas9-mediated eGFP reporter integration in zebrafish

Abstract: The CRISPR/Cas9 complex, which is composed of a guide RNA (gRNA) and the Cas9 nuclease, is useful for carrying out genome modifications in various organisms. Recently, the CRISPR/Cas9-mediated locus-specific integration of a reporter, which contains the Mbait sequence targeted using Mbait-gRNA, the hsp70 promoter and the eGFP gene, has allowed the visualization of the target gene expression. However, it has not been ascertained whether the reporter integrations at both targeted alleles cause loss-of-function p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 26 publications
0
31
0
Order By: Relevance
“…In contrast, recently, Ota et al (2016) have reported a similar strategy to knock-in eGFP at the same genomic locus for pax2a , but the knocked-in allele generated a pax2a mutant allele resembling the homozygous pax2a null allele, no isthmus ( noi ; Brand et al, 1996). Differences in bait construction might account for why our strategy did not result in null alleles, compared to Ota et al (2016).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, recently, Ota et al (2016) have reported a similar strategy to knock-in eGFP at the same genomic locus for pax2a , but the knocked-in allele generated a pax2a mutant allele resembling the homozygous pax2a null allele, no isthmus ( noi ; Brand et al, 1996). Differences in bait construction might account for why our strategy did not result in null alleles, compared to Ota et al (2016).…”
Section: Discussionmentioning
confidence: 99%
“…In cep55 uy25 mutant embryos (n = 7), the islet1-positive motor neurons in the spinal cord were detected to be normal, whereas islet1-positive cranial motor neurons in the brain were reduced and disorganized (Figure 6b,d). Next, we used the cep55 uy25 mutant possessing the transgene pax2-hs:EGFP, which widely visualizes some regions of the midbrain, cerebellar primordium and hindbrain (Ota et al, 2016). We found that the pax2-positive cells in the isthmocerebellar were reduced in the cep55 uy25 mutant embryos (n = 5) compared to wild-type embryos (n = 10; Figure S5).…”
Section: F I G U R Ementioning
confidence: 96%
“…The otx2 expression domain was narrow in the cep55 uy25 mutant embryo. Next, we used the cep55 uy25 mutant possessing the transgene pax2-hs:EGFP, which widely visualizes some regions of the midbrain, cerebellar primordium and hindbrain (Ota et al, 2016). In wild-type embryos (n = 8), GFP expression was detected in the motor neurons in the midbrain (nIII neurons and nIV neurons), in the branchiomotor neurons in the hindbrain (nV neurons, nVII neurons and nX neurons) and in the motor neurons of the spinal cord (Figure 6a,c).…”
mentioning
confidence: 99%
“…When the donor vector was co-injected with Cas9 mRNA and 2 sgRNAs (targeting for the pax2a locus and for the donor vector) into zebrafish embryos, the eGFP expression in some of the injected F0 embryos partially overlapped with the pax2a expression domains. 28 We established the transgenic line Tg[pax2a-hs:eGFP], showing that the eGFP expression in the heterozygous embryos completely overlaps the endogenous pax2a expression domains 28 (Fig. 4B (i)).…”
Section: Nhej-mediated Reporter Knock-in To Visualize and Disrupt Thementioning
confidence: 99%
“…We have also reported that the NHEJ-mediated integration of the reporter gene into the start codon is useful to monitor the expression pattern of an uncharacterized gene (epdr1: ependymin related 1) in the heterozygous embryos and to analyze the loss-of-function phenotypes in the homozygous embryos. 28 Recently, Hoshijima et al have demonstrated reporter gene insertion just downstream of the start codon of the potassium voltage-gated channel subfamily H member 6a (kcnh6a) gene in zebrafish using TALEN system. 29 The kcnh6a gene is exclusively expressed in the heart, and its disruption causes a cardiac disorder.…”
Section: Nhej-mediated Reporter Knock-in To Visualize and Disrupt Thementioning
confidence: 99%